2016
DOI: 10.1242/dmm.024950
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of vascular endothelial growth factor signaling facilitates liver repair from acute ethanol-induced injury in zebrafish

Abstract: Alcoholic liver disease (ALD) results from alcohol overconsumption and is among the leading causes of liver-related morbidity and mortality worldwide. Elevated expression of vascular endothelial growth factor (VEGF) and its receptors has been observed in ALD, but how it contributes to ALD pathophysiology is unclear. Here, we investigated the impact of VEGF signaling inhibition on an established zebrafish model of acute alcoholic liver injury. Kdrl activity was blocked by chemical inhibitor treatment or by gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 70 publications
0
21
0
Order By: Relevance
“…A‐SC). To investigate the effects of MPI loss on HSC activation, we isolated livers from control and mpi MO embryos at 5 dpf and used qRT‐PCR to measure expression of genes reflecting activation of fibrotic response . Gene expression for the ECM proteins, collagen, type I, alpha 1b ( col1a1b ), actin, alpha 2, smooth muscle ( acta2 ), platelet‐derived growth factor receptor beta ( pdgfrb ), laminin subunit beta 4A ( lamb4a ), and tissue inhibitor of metalloproteinases 2 ( timp2b ), were significantly increased in mpi MO livers (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A‐SC). To investigate the effects of MPI loss on HSC activation, we isolated livers from control and mpi MO embryos at 5 dpf and used qRT‐PCR to measure expression of genes reflecting activation of fibrotic response . Gene expression for the ECM proteins, collagen, type I, alpha 1b ( col1a1b ), actin, alpha 2, smooth muscle ( acta2 ), platelet‐derived growth factor receptor beta ( pdgfrb ), laminin subunit beta 4A ( lamb4a ), and tissue inhibitor of metalloproteinases 2 ( timp2b ), were significantly increased in mpi MO livers (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21] In the current study, we combined the padlock probe technology with multiplex real-time PCR to detect genetic mutations, and demonstrated the feasibility, great specicity and high sensitivity of the assay.…”
Section: 12mentioning
confidence: 99%
“…Transgenic lines that express fluorescent proteins in hepatocytes, intrahepatic biliary cells, endothelial cells, and hepatic stellate cells are available, facilitating the observation of these cells both in live fish and in fixed livers (Table 1). These transgenic zebrafish also allow isolation of different liver cell types through fluorescence activated cell sorting for downstream transcriptome analyses [16]. Commercially available fluorescent lipid analogs, which are designed for visualizing lipid uptake and processing in live fish, have proven to be extremely sensitive in detecting hepatobiliary injuries (Table 1).…”
Section: Tools To Study Liver Pathophysiology In Zebrafishmentioning
confidence: 99%
“…Genes and pathways necessary for alcohol metabolism are highly conserved in zebrafish and they readily take up and metabolize alcohol at as early as 4 days post fertilization [62, 61, 63, 64]. Intriguingly, exposing 4-day-old larvae to 2% ethanol for just 24 hours is sufficient to induce steatosis, angiogenesis, recruitment of macrophages, and activation of hepatic stellate cells [61, 15, 16]. Using this model, the Sadler group showed that the sterol response element binding protein (Srebp) pathway [61] and activation of unfolded protein response (UPR) were required to induce hepatic steatosis in acute ALD liver injury [65, 66].…”
Section: Zebrafish Models Of Liver Diseasesmentioning
confidence: 99%
See 1 more Smart Citation